Pirfenidone in patients with unclassifiable progressive fibrosing interstitial lung disease: design of a double-blind, randomised, placebo-controlled phase II trial - Maher, Toby M.; Corte, Tamera J.; Fischer, Aryeh; Kreuter, Michael; Lederer, David J.; Molina-Molina, Maria; Axmann, Judit; Kirchgaessler, Klaus-Uwe; Cottin, Vincent (BMJ Open Respiratory Research, 2018)
Introduction Despite extensive multidisciplinary team (MDT) assessment, some patients have interstitial lung disease (ILD) that is considered unclassifiable (uILD), for which there are currently no approved treatments. This study will assess the efficacy and safety of the antifibrotic pirfenidone in treating uILD. - Methods and analysis This double-blind, randomised, placebo-controlled phase II trial is enrolling adults with fibrosing ILD, including uILD that fulfils proposed research criteria for interstitial pneumonia with autoimmune features (IPAF), that cannot be classified with moderate or high confidence to any category of ILD following MDT discussion. Study participants must have >10% fibrosis on high-resolution CT scan within the previous 12 months, forced vital capacity (FVC) ≥45% and diffusing capacity of the lung for carbon monoxide ≥30% of predicted values. Study participants will be randomised to receive 801 mg pirfenidone or placebo three times daily for 24 weeks. The efficacy of pirfenidone vs placebo will be assessed by daily measurement of FVC using a handheld spirometer over the treatment period. Other functional parameters, patient-reported outcomes, samples for biomarker analysis and safety endpoints will be collected. Additionally, the study will assess the efficacy and safety of pirfenidone with and without concomitant mycophenolate mofetil treatment and in study participants with or without IPAF. - Ethics and dissemination This trial is being conducted in accordance with the International Conference on Harmonisation E6 guideline for Good Clinical Practice, Declaration of Helsinki and local laws for countries in which the research is conducted. - Trial registration number NCT03099187.
Gesehen am 12.09.2019